Teknik Psikoanalisa dalam Konseling Kelompok - Habsy, Bakhrudin All; Azmil, Ulil; Anggraeny, Trya Ayu; Febriani, Dwita; Wulandari, Dewi Putri (TSAQOFAH, 2024)
Psychoanalytic theory is a theory that attempts to explain the nature and development of human personality. The main elements in this theory are motivation, emotions and other internal aspects. This theory assumes that personality will develop if there are various conflicts from these psychological theory based on psychoanalytic analysis is that the counselor guides the counselee to understand what the counselee wants to achieve, the activities they will carry out, and the progress that the counselee has achieved. In group counseling, counselees can use interactions with other counselees in the group to help increase understanding of certain values and goals as well as to learn or eliminate certain attitudes and behavior.